Revitalizing quality of life in Union, Nebraska through implementation of sustainable community amenities and brownfield remediation - Kisler, Stephanie (Kansas State University, 2013)
This document is a Master’s Project for a proposal of a sustainable community amenity to be implemented in Union, Nebraska. The idea that I have considered best fit for Union is the concept of a multi-functional structure that will have many uses, such as office space for city government, a community center, a visitor center, public restrooms, and indoor and outdoor recreational space. There may also be space that can be utilized for a small commercial function, such as a coffee shop, bakery, or convenience store. Right now, Union only has a handful of businesses, most of which only operate part-time. There is nowhere currently where a person can purchase a drink, a meal, groceries, or even use a restroom. Although Union lacks those amenities, Union is home to two historic finds: an old Union Pacific Railroad caboose car and a single-room jail cell. Without a proper place to showcase Union’s unique character or a place for people to stop in the town, Union may take a turn downhill economically and socially. Many sites in the town are deteriorating and are in definite need of rehabilitation. The implementation of the proposed structure will improve the quality of life for the community as well as benefit passersby by providing an attraction. The social equity of the community is an important concern and providing a space where the community can thrive within Union is an integral factor for sustainability in the town. By also targeting the people driving through Union, the town can benefit economically by getting these visitors to stop and spend money in the town. Environmentally, Union can be improved by addressing the aging properties along their main street. Many parcels along Main Street are potential brownfield sites and could be revitalized through cleanup funding opportunities. Within this document I will be identifying potential sites and funding opportunities and focusing on composing a feasible course of action for implementing the multi-functional structure. Research has been done through many methods including literature reviews, case studies, site visits, and through a community survey process. Funding for my research is provided by the Technical Assistance to Brownfields (TAB) program through the Environmental Protection Agency (EPA) because of the potential brownfield interests in Union. Working with Union, Nebraska constitutes a valid planning situation because it is in need of essential planning practices that can boost the social, economic and environmental equity of the town. With only about 230 residents, Union has only one governmental official, the city clerk. The city clerk must wear many hats in order to keep Union running smoothly. Having help with planning recommendations will greatly benefit the town and take some weight off of the city clerk’s work load. By focusing my efforts on creating a concept for a multi-functional building, I could produce the optimum outcome in the most efficient manner. The final goal of my work is to not only graduate with a Master’s Degree in Regional and Community Planning through the College of Architecture, Planning and Design at Kansas State University, but also to impact the town of Union, Nebraska in a positive and lasting way. I am truly pleased to be able to produce something that could improve the quality of life in a realistic way for a real community. If I can use this project to make any positive influence in a community, then I have succeeded.
Keywords: Planning; Quality of Life; Community; Rural; Amenities; Brownfield; Area Planning and Development (0341); Land Use Planning (0536); Social Research (0344)